Nature of viruses and the radical change in viral taxonomy - V. V. Makarov; L. P. Buchatsky (Ветеринария сегодня)
A short report is devoted to the radical changes in the taxonomy of viruses. The metagenomic sequencing has revealed the presence of a vast variety of viruses in diverse environmental samples without any connections with banal parasitism, infectivity, or pathogenicity. The understanding of viruses has expanded beyond the original parasitic–pathogen model, and now virologists recognize the role of viruses in host regulation and the maintenance of natural ecosystems. Co-evolution of the viral and cellular genomes includes mutual horizontal gene transfer and joint development of new biological functions, such as the mechanism of phylogenesis and phylodynamics of coactants. The concepts of the origin of viruses and their relation to the Universal Tree of Life are formulated. In this regard, the International Committee on the Taxonomy of Viruses (ICTV) changed the previous Code of their classification hierarchy from five ranks to a fifteen-rank one, that emulates a Linnaean framework and accommodates the entire spectrum of genetic divergence in the virosphere. Changes in the rank hierarchy are based on the evolution of the recognition of virus taxa over time, from a traditional phenotype-based characterization process to a multistage process that includes comparative sequence analyses of conserved genes and proteins, including gene phylogeny, gene synteny and shared gene content. The ICTV, that oversees the official classification of viruses and nomenclature of taxa, accepts possible non-hierarchical classifications of viruses beyond taxonomic attribution. The above provisions are illustrated with schemes of chimeric polyphyletic origin of viruses and a new rank structure; the table gives examples of the modern classification of viruses that cause some socially significant infections.